The Causes of Secularization by Christopher Dawson - Bartulica, Stephen Nikola (Poznańskie Studia Slawistyczne, 2016)
The article examines the root causes of the secularization of European culture by focusing on the writings of the English historian Christopher Dawson. Dawson’s central argument is that every human culture is based on religion and, thus, European culture on Christianity. He identifies the root causes of secularization to be found in the Renaissance and Protestant Reformation movements, both of which facilitated the emergence of the modern nation-state, but in different ways. The Renaissance marked the coming of a new culture – a new way of life – which had its roots deep in the past and had been developing for centuries in the Mediterranean world. The Protestant Reformation, on the other hand, brought an end to the religious unity which had existed for centuries in Western Europe, and subsequently divided Europe along religious lines. These two movements essentially laid down the foundations of an alternative culture, one often unbeknown to its architects: a culture which was still very much influenced by Christian origins, but would become over time first the rival and later the successor of Christianity.